Protekcjonizm agrarny, a rozwój przemysłu w Królestwie Prus w drugiej połowie XIX w. i początkach XX w. na przykładzie prowincji Pomorze - Myszczyszyn, Janusz (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The German and Prussian economy is an example of the growing economic integration of many of the sovereign states within the German Customs Union (1834). After 1879 the German Empire changed its trade policies from liberal to protectionist (high tariffs on agricultural and industrial products), like many other European countries. High tariffs policy, provided a much higher income landlords and heavy industries, such as other limited inflow of cheap foreign grain, livestock meant rising prices, increased cost of living. Prussian Junkers thus contributed to lower economic development regions of eastern Germany and prevent the outflow of labor to the cities, making it difficult for industry development initiative. High tariffs have delayed or prevented the tendency to make the necessary changes in the nature of farming – increasing the importance of animal husbandry, special branches of agricultural production (of which there is for example in England), greater intensification. Province of Pomerania, missed the chance build industrial and agricultural region. Only the big resorts like Szczecin experienced growth in the industrial sector and service sector. Prussian government policies (including the Junkers) to Pomerania, was different from the needs of economic development of the region. The region remained economically backward compared to the western provinces of the Reich.